Protocells: Milestones and Recent Advances (Small 18/2022). Issue 18 (5th May 2022) - Gözen, Irep; Köksal, Elif Senem; Põldsalu, Inga; Xue, Lin; Spustova, Karolina; Pedrueza‐Villalmanzo, Esteban; Ryskulov, Ruslan; Meng, Fanda; Jesorka, Aldo
Abstract : Protocells Approximately 4 billion years ago, protocells are thought to have emerged as a precursor to life. In article number 2106624, Irep Gözen and co‐workers introduce protocell concepts, research and laboratory methods.